Novel multi-stage aluminium production: part 2 – experimental investigation on carbosulphidation of Al2O3 using H2S and sodiothermic reduction of Al2S3 - Huda, N.; Khaliq, A.; Rhamdhani, M.; Sheppard, Drew; Brooks, G.; Monaghan, B.; Prentice, L. (Maney Publishing, 2017)
In this paper, experimental investigation on the carbosulphidation of alumina (Al2O3) for aluminium (Al) production and the sodiothermic reduction of aluminium sulphide (Al2S3) are presented. Hydrogen sulphide (H2S) was used as a reductant and source of sulphur. This work is the second of two-parts paper series. The experimental investigations of the Stage-1 process (Al2O3 carbosulphidation) were carried out at 1100–1600°C using a laboratory scale horizontal tube resistance-furnace. H2S gas, diluted with argon (5% H2S and 95% Ar), was reacted with pellets of a mixture of γ-Al2O3 and C powders (1:6 molar ratio) to produce Al2S3. The effects of gas injection rate, pelletizing pressure, temperature and reaction time on the conversion of Al2O3 to Al2S3 were investigated. The X-ray diffraction results confirmed the formation of Al2S3(s) in the reaction product above 1400°C. The conversion of Al2O3 to Al2S3 was found to be 99.5% at 1600°C and 12 h. The kinetics analysis of alumina sulphidation using Ginstling-Brounshtein diffusion model suggested the overall reaction was controlled by the diffusion of H2S gas through the reaction product (liquid Al2S3). The activation energy of the alumina sulphidation reaction was calculated to be 148.5 kJ mol−1. It has also been demonstrated in this study that Al can be extracted from Al2S3 by sodiothermic reduction using Na or NaH. In the case of Na, a level of Al conversion of 75% has been observed for reaction at 290°C.